Mutagenic Effectiveness of EMS, MMS and Gamma Rays in Niger (Guizotia abyssinica Cass.) - Maloo, S R; Aggarwal, P K (Annals of Arid Zone, 2016)
Seeds of niger cv., UN-4 were treated with two doses of EMS, MMS and gamma rays. In M1 generation variable response of metagens was observed for different characters. Plants appearing normal were selected from each treatment and advanced to M2 generation. The estimates of GCV, heritability and genetic gain were high in the mutagenic lines of EMS (0.25% followed by 0.50%) and gamma rays (20 kR ). EMS was the most effective at lower doses in both the generations.